2015
DOI: 10.1016/j.foreco.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Status and trends in global primary forest, protected areas, and areas designated for conservation of biodiversity from the Global Forest Resources Assessment 2015

Abstract: a b s t r a c tThe global community has recognized the importance of forests for biodiversity, and has prioritized the preservation of forest biodiversity and ecosystem functions through multiple multilateral agreements and processes such as the Convention on Biodiversity's Aichi Targets and the Millennium Development Goals. The Global Forest Resources Assessment (FRA) provides one mechanism for tracking progress toward such goals in three particular areas: primary forest area, protected forest areas, and area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(130 citation statements)
references
References 26 publications
4
115
1
3
Order By: Relevance
“…We found that NNR lost > 100 km 2 of forest cover amounting to ~ 1 per cent of its aggregated forest extent. This may appear substantial, but is much lower than the 3 per cent of forest cover lost in protected areas globally during the same time period (Heino et al, 2015;Morales -Hidalgo et al, 2015). Our findings are also particularly encouraging in the African context, given deforestation rates on the continent are five times higher than the global average (Tranquilli et al, 2014), and there are many examples of protected areas in Africa losing much more forest cover within their boundaries (Bowker et al, 2017;Allan et al, 2017;Sassen et al, 2013).…”
Section: Discussionsupporting
confidence: 53%
“…We found that NNR lost > 100 km 2 of forest cover amounting to ~ 1 per cent of its aggregated forest extent. This may appear substantial, but is much lower than the 3 per cent of forest cover lost in protected areas globally during the same time period (Heino et al, 2015;Morales -Hidalgo et al, 2015). Our findings are also particularly encouraging in the African context, given deforestation rates on the continent are five times higher than the global average (Tranquilli et al, 2014), and there are many examples of protected areas in Africa losing much more forest cover within their boundaries (Bowker et al, 2017;Allan et al, 2017;Sassen et al, 2013).…”
Section: Discussionsupporting
confidence: 53%
“…Forests with limited human intervention, whether "pristine", ancient or old growth, are a limited and diminishing feature of modern landscapes [1,2]. They are essential in terms of conserving biodiversity, climate change mitigation, or as reference systems for forest management or restoration [3].…”
Section: Introductionmentioning
confidence: 99%
“…The loss of biodiversity is perhaps the most frequently addressed consequence of deforestation in tropical forests [12,13]. However, these ecosystems are also important reservoirs of carbon with averages between 200 and300 Mg C ha −1 in the aboveground biomass (AGB) [14].…”
Section: Introductionmentioning
confidence: 99%